The impact of pathogenic tumor mutation status on high grade serous epithelial ovarian cancer survival outcome: A multicenter study from Indonesia - Sutrisno Sutrisno; Dina Marlina; Kevin Dominique Tjandraprawira; Putri Nadhira Adinda Adriansyah (SAGE Open Medicine)
Introduction: Ovarian cancer is still a major health problem in Indonesia. development of breast cancer gene-related personalized medicine to increase the survival outcome of epithelial ovarian cancer patients in Indonesia is expected to be achieved. This research aims to evaluate the impact of pathogenic breast cancer gene 1 and breast cancer gene 2 tumor mutation on high-grade serous epithelial ovarian cancer survival outcome. Methods: This study is an observational analytic study, using a historical cohort study design. A total of 68 from 144 patients diagnosed with International Federation of Gynecology and Obstetrics 2014 stage IIB-IV high-grade serous epithelial ovarian cancer between January 1st, 2015 until March 31st, 2021, at three centers in Jakarta. Next-generation sequencing tumor breast cancer gene 1 and breast cancer gene 2 testing and were included in this cohort historical study. We compared patient’s overall survival outcomes, according to pathogenic breast cancer gene 1 and breast cancer gene 2 tumor mutational status. Clinicopathological characteristic factors that might affect patient’s survival outcomes were also investigated. Results: In the group of individuals with pathogenic breast cancer gene 1 and breast cancer gene 2 tumour mutations, the risk of death was significantly lower by 86% (adjusted RR 0.149; 95% CI: 0.046–0.475; p -value = 0.001), and the median survival time was significantly better (median 46 months; 95% CI: 34.009–57.991; p -value = 0.001) compared to the group without pathogenic breast cancer gene 1 and breast cancer gene 2 tumor mutations (median 23 months; 95% CI: 15.657–30.343; p -value = 0.001). The multivariate analysis revealed that the presence of a pathogenic breast cancer gene 1 and breast cancer gene 2 tumor mutation is an independent and positive prognostic factor for survival outcome. The adjusted relative risk was 0.149, with a 95% CI of 0.046–0.475, p -value = 0.001. Conclusions: In high-grade serous ovarian cancer patients, the pathogenic breast cancer gene 1 and breast cancer gene 2 tumor mutations group have a better prognosis with longer survival outcomes than those without pathogenic breast cancer gene 1 and breast cancer gene 2 tumor mutations.